Saturation of Alfvén modes in tokamaks. (20th September 2016) - White, Roscoe; Gorelenkov, Nikolai; Gorelenkova, Marina; Podesta, Mario; Ethier, Stephane; Chen, Yang
Abstract: Growth of Alfvén modes driven unstable by a distribution of high energy particles up to saturation is investigated with a guiding center code, using numerical eigenfunctions produced by linear theory and a numerical high energy particle distribution, in order to make detailed comparison with experiment and with models for saturation amplitudes and the modification of beam profiles. Two innovations are introduced. First, a very noise free means of obtaining the mode-particle energy and momentum transfer is introduced, and secondly, a spline representation of the actual beam particle distribution is used.